2018
DOI: 10.1080/02688697.2018.1424320
|View full text |Cite
|
Sign up to set email alerts
|

Development of three-dimensional brain arteriovenous malformation model for patient communication and young neurosurgeon education

Abstract: Patient-specific 3D printed models of brain AVM can be constructed with high fidelity. 3D printed brain AVM models are proved to be helpful in preoperative patient consultation, surgical planning and resident training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…3D models, highlighted herein, are significantly more expensive on a caseby-case basis than conventional equivalents, particularly when personalised to specific procedures or specific patient pathology. 13 Importantly, however, this is not uniformly the case when adopting digital platforms and a number of studies, including those by Thapa et al and Macyszyn et al, have demonstrated considerable net savings. 19,26 This has typically been through either low upfront costs associated with communication tools or organisational savings attributed to improved clinical outcomes or preventing the need for duplicate investigations, as is often the case in current clinical practice.…”
Section: Barriers To Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…3D models, highlighted herein, are significantly more expensive on a caseby-case basis than conventional equivalents, particularly when personalised to specific procedures or specific patient pathology. 13 Importantly, however, this is not uniformly the case when adopting digital platforms and a number of studies, including those by Thapa et al and Macyszyn et al, have demonstrated considerable net savings. 19,26 This has typically been through either low upfront costs associated with communication tools or organisational savings attributed to improved clinical outcomes or preventing the need for duplicate investigations, as is often the case in current clinical practice.…”
Section: Barriers To Implementationmentioning
confidence: 99%
“…Here both CT angiography and aneurysm clip data was uploaded to a virtual workstation and used to simulate clip placement from an array of different approaches, allowing surgeons to better understand potential exposure and obliteration of an aneurysm. Further work by Dong et al and Alaraj et al built on this, adding in real-time haptic feedback and concluding that these tools provided a close resemblance to real operative anatomy and accurate guidance for deciding surgical approaches 5,13. A similar study by Alsofy et al again used CT angiography to develop anatomically accurate 3D models of 26 pre-operative patients.…”
mentioning
confidence: 99%
“…Some institutions are starting to model and print VMs integrating them into hydraulic circuits to create the most realistic representation of real VMs 97 . These printed models allow a more accurate planning of surgical and interventional procedures, and selecting the most appropriate approach 98 . 3D modeling is also able to reduce the learning curve of less experienced operators, helping them to train and gaining confidence with their procedures.…”
Section: Present and Future Insightsmentioning
confidence: 99%
“…44 Additive manufacturing technology is used to manufacture 3D models of the AVM and to facilitate the preoperative conversation with the patient and to serve as medical education for young surgeons. 45,46 Carotid endarterectomy (CE) has also entered the AM era. Before the advent of AM, CE depended on the patients' surgical exposition.…”
Section: Additive Manufacturing In Neurosurgerymentioning
confidence: 99%